Analisis Peran Guru dalam Minat Baca Pada Siswa Kelas IV Di SDN Genukwatu II - Maria Ulfa; Tyasmiarni Citrawati (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the role of teachers in reading interest in fourth grade students. This type of research is qualitative descriptive research. The subject of this research is a class IV teacher. The data collection techniques used were interview and observation techniques. The results of the research are, 1) The role of the teacher as a motivator, the efforts made by the teacher as a motivator are by providing support to students, 2) The role of the teacher as a guide, namely by familiarizing students with reading, 3) The role of the teacher as a facilitator, namely by providing infrastructure , 4) The teacher's role as a model and role model, namely by providing examples so that students have an interest in reading. The conclusion of this research is that the teacher's role in reading interest in class IV students, namely as a motivator, guide, facilitator, and as a model and role model has been carried out well, but there are several roles that have not been implemented optimally. It is hoped that teachers will be more optimal in implementing it.